ByzRev 03.2021.016: Andrea Olsen Lam – Rossitza Schroeder (eds.), The Eloquence of Art: Essays in Honour of Henry Maguire: (Birmingham Byzantine and Ottoman Studies s.n.). Abingdon – New York: Routledge 2020. - Parpulov, Georgi (The Byzantine Review, 2021)
Andrea Olsen Lam – Rossitza Schroeder (eds.), The Eloquence of Art: Essays in Honour of Henry Maguire (Birmingham Byzantine and Ottoman Studies s.n.). Abingdon – New York: Routledge 2020. xxxvi, 437 pp. – ISBN: 978-0-8153-9459-4 (hardback, £ 96.00), 978-1-351-18559-2 (ebook, £ 29.59)